Electrochemically generation of hydrogen peroxide from molecular oxygen by BaSm2O4/carbon composite. (2021) - Ranjan Mahalik, Rakesh; Parhi, Purnendu
Abstract: Moving electrochemical oxygen reduction from 4 e- process towards 2e – pathway for hydrogen peroxide (H2 O2 ) generation from molecular oxygen is an important green chemistry pathway for generation of H2 O2 . In this paper, we have prepared BaSm2 O4 by simple sol–gel method, which shows potential activity as an electrocatalyst for large scale production of H2 O2 . BaSm2 O4 prefers the two electron pathway rather than four electron pathway which is not seen in other rare earth based spinels. In order to enhance the electrochemical oxygen reduction reaction (ORR) pathway we prepared BaSm2 O4 and vulcan carbon composite with different weight percentage (20%, 40%, 60% and 80%). The selectivity for H2 O2 production was further increased by the addition of vulcan carbon (VC) matrix to BaSm2 O4 . It was found that BaSm2 O4 /VC composites prefer 2-electron pathway and generates 88%–93% H2 O2 . Tafel slopes and rate constants were studied in order to compare the ORR kinetics for the prepared catalysts.